Impact of co-morbidities in COVID -19 infected patients - Verma , Preeti; Chaudhary, Sachin; Kaur, Samarjeet; Midha, Tanu; Martolia, Dinesh Singh (Indian Journal of Community Health, 2022)
Background- During the COVID- 19 pandemic in the first wave, infected patients age was range from 4 weeks to 90 years and those who have more age and with comorbidities are more susceptible to develop serious illness and have high mortality rates. Objective-To study the association between survivor vs non survivor on the basis of demographic profile and high risk factors. Material & methods: This study was done in the Government Medical College, Kannauj on the COVID-19 patients who were admitted in the isolation wards, from 1st September 2020 to December 31st 2020. Statistical Analysis- Analysis was done using SPSS- 23 trial version software. Results: case fatality rate was 2.7% in this study. Most common symptoms was cough (61.0%) and among these admitted patients the most common comorbidities was hypertension (26.7%), followed by diabetes (20.7%), and COPD (14.0%) respectively. Platelets (< 0.02), post prandial blood sugar (PPBS) (< 0.01) have significant role in survivability of COVID- 19 patients. Conclusion: This study concludes that those patients who were older in age and with comorbidity especially (hypertension, COPD, high PPBS, High platelets) have poorer prognosis as compare to those without.